Eddie's toolbox : and how to make and mend things - Garland, Sarah (London : Frances Lincoln Children's Books, 2010)
Eddie learns how to use different kinds of tools while helping his new neighbor, Tom, around the house, and receives a special surprise as a reward for all his hard work.
2.9
K-3
K-3
Keywords: Friendship -- Juvenile fiction; Home economics -- Juvenile fiction; Neighbors -- Juvenile fiction; Woodwork -- Juvenile fiction; Friendship -- Fiction; Home economics -- Fiction; Neighbors -- Fiction; Woodwork -- Fiction; Friendship -- Fiction; Home economics -- Fiction; Neighborhoods -- Fiction; Woodwork -- Fiction; Picture books for children